THE USE OF THE DISCOVERY LEARNING MODEL IN IMPROVING THE QUALITY OF LEARNING OF ISLAMIC ELEMENTARY SCHOOL STUDENTS - Al Muftiyah, Al Muftiyah; Handayani, Suci; Aflaha, Dwi Sari Ida; Saputra, Aswin; Solihah, Fatimatus (Jurnal Konseling Pendidikan Islam, 2024)
The aim of this research is to provide a reference for learning approaches that are proven to improve student academic achievement in Islamic elementary schools. This research uses meta-analysis to collect findings from other studies sourced from the same literature: five case studies of students using the Discovery Learning learning paradigm published in the national journal of the Higher Education Accreditation Board (Kemenristek Dikti). This research found that the use of the discovery learning paradigm to improve student learning outcomes in Islamic elementary schools is very effective, especially in increasing student achievement in these subjects. Therefore, the Discovery Learning teaching methodology is integrated into teacher-led lesson plans, thus having an impact on students' ability to deepen their understanding of the lesson material.